2010
DOI: 10.5423/ppj.2010.26.1.057
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antioxidant Properties of Secondary Metabolites from White Rose Flower

Abstract: Low-molecular-weight secondary metabolites from plants play an important role in reproductive processes and in the defense against environmental stresses or pathogens. In the present study, we isolated various volatiles and phenolic compounds from white Rosa rugosa flowers, and evaluated the pharmaceutical activities of these natural products in addition to their ability to increase survival in response to environmental stress and pathogen invasion. The DPPH and hydroxyl radical-mediated oxidation assay reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…In our previous study, we determined that the hexane fraction of the white rose fl ower extract contained various functional volatiles (Table 2) and the abundant amount of total polyphenols (330.3 ± 20.1 mg of gallic acid equival/g of dry weight), which was approximately 2-fold higher than the amount observed in the butanol fraction and 2.6-fold higher than the amount observed in the water fraction Joo et al, 2010). These results suggested that the hexane fraction from white rose fl ower extracts may have a more potent functional activity and, thus, was selected for more indepth anti-infl ammatory analysis (Joo et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our previous study, we determined that the hexane fraction of the white rose fl ower extract contained various functional volatiles (Table 2) and the abundant amount of total polyphenols (330.3 ± 20.1 mg of gallic acid equival/g of dry weight), which was approximately 2-fold higher than the amount observed in the butanol fraction and 2.6-fold higher than the amount observed in the water fraction Joo et al, 2010). These results suggested that the hexane fraction from white rose fl ower extracts may have a more potent functional activity and, thus, was selected for more indepth anti-infl ammatory analysis (Joo et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…These results suggested that the hexane fraction from white rose fl ower extracts may have a more potent functional activity and, thus, was selected for more indepth anti-infl ammatory analysis (Joo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of such problems, in vitro culture of L. iberica turns out to be a fundamental system in comparison with its cultivation in natural conditions. Secondary metabolites are generally natural components of plants with low molecular weight (Joo et al 2010). It has been shown that the phenolic compounds, especially flavonoids, have protective effects against the development of chronic diseases containing cardiovascular diseases, cancers, diabetes, aging, asthma, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of chemicals have been obtained from plants, including ginsenosides, paclitaxel, echinacosides, shikonin, berberine and hypericin [20][21][22][23]. These compounds are involved in the elimination of toxic free radicals, enzyme activation, activation of immune system, controlling the expression of genes and cell death initiation [24,25]. These bioactive compounds also function as nutraceuticals, to cure cardiac diseases, flavor foods, provide antioxidants, create potential drugs, supply pharmaceuticals and act as anticarcinogens.…”
Section: Introductionmentioning
confidence: 99%